2016
DOI: 10.1002/bjs.10289
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of aberrant lymphatic drainage in recurrent breast cancer

Abstract: Lymphatic mapping is feasible in recurrent breast cancer. It avoids ALND in over 50 per cent of patients who have undergone SNB, and allows the 4 per cent of patients with metastatically involved aberrant nodes to receive targeted surgical and adjuvant therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 31 publications
1
17
0
1
Order By: Relevance
“…In patients with a positive rSLNB, the incidence of an aberrant node being the site of regional metastatic disease is fairly high, at approximately 40% (range 20-72%). [2][3][4] Poodt et al previously reported a low risk of regional recurrence in the setting of a negative SLNB, 5 and herein report a low risk of regional recurrence if lymphatic mapping fails. 1 Importantly, if there is a regional failure, many occur outside the ipsilateral axilla (supraclavicular, internal mammary and contralateral axilla).…”
supporting
confidence: 56%
“…In patients with a positive rSLNB, the incidence of an aberrant node being the site of regional metastatic disease is fairly high, at approximately 40% (range 20-72%). [2][3][4] Poodt et al previously reported a low risk of regional recurrence in the setting of a negative SLNB, 5 and herein report a low risk of regional recurrence if lymphatic mapping fails. 1 Importantly, if there is a regional failure, many occur outside the ipsilateral axilla (supraclavicular, internal mammary and contralateral axilla).…”
supporting
confidence: 56%
“…A few reports have discussed the contralateral axillary in re-SLNB patients with isolated IBTR [14][15][16][17]. Cordoba et al [18] reported that 54 patients with IBTR received re-SLNB.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, exploration of SLNs in lymph node basins other than the ipsilateral and contralateral axilla is not recommended during rSLNB. Surgical exploration of aberrant nodes is more difficult, with potential additional morbidity (including risk of nerve injury, pneumothorax and bleeding) and there is currently insufficient evidence to recommend extra‐axillary SLNB.…”
Section: Discussionmentioning
confidence: 99%